Proximate and Phytochemical Profile of Ethanol Extracts from Seeds and Pulps of Artocarpus. Heterophyllus - Habiganuchi, A; Monago-Ighorodje, C; Olua, V; Amadi, Chigozirim Steve; Ibiama, Boma, G.; Habiganuchi, O.; Ajie, B. I. (European Journal of Applied Sciences, 2024)
The Proximate and phytochemical potentials of the seeds and pulp of Artocarpus heterophyllus were evaluated to unravel reasons behind their wild usages locally for treatment of several diseases. The phytochemical and proximate compositions of the seed and pulp were determined using standard laboratory methods. The result shows that in pulp, flavonoids (98.11ppm), were the highest phytochemicals present, followed by alkaloids (24.86ppm), and Tannin (22.59). This shows that the pulp contains more phytochemicals (234.19ppm) than the seeds (160.25). The proximate profile gave maximum carbohydrate (%) for seed and pulp respectively as 52.68 and 56.6, followed by protein (%) as 24.13 and 18.85 for seed and pulp. This research work shows that it is clear that both the seed and pulp of A.heterophyllus have essential potential ingredients that could be used in management of several diseases, fungal and bacterial infections. The assayed proximate profile showed high Carbohydrate, protein and fibre content. Making this samples good carbohydrate, protein and fibre sources.